Government in Passport Services at Class I Immigration Office Central Jakarta City - Tama, Tomas Aditia; Achmad, Mansyur; Nurdin, Ismail (Blantika: Multidisciplinary Journal, 2025)
This study examines the impact of increasing applicants on passport services at the Class I Central Jakarta Immigration Office, particularly during peak hours, when long queues often occur, leading to delays and decreased public satisfaction. High pressure on officers during these periods can reduce service quality and increase the risk of administrative errors. The research employs a qualitative descriptive approach, utilizing Indrajit's (2006) e-government theory, with primary data collected from interviews, observations, and documentation involving 17 informants, as well as secondary data sources. Data analysis was conducted using techniques such as data reduction, data presentation, and conclusion drawing. The findings reveal that e-government services at the Immigration Office are supported by adequate telecommunication infrastructure, including high-speed internet and modern hardware/software. The use of online service applications facilitates real-time, transparent passport applications, thereby improving public access and enabling effective monitoring. Human resources in the office demonstrate strong readiness for digital transformation, supported by routine training and digital literacy programs. Budget management is efficient, supporting infrastructure procurement, application development, and employee training. Legal frameworks, including laws, government regulations, and internal Standard Operating Procedures (SOPs), provide comprehensive guidance for e-government services, ensuring personal data protection and procedural accountability. Additionally, the shift from conventional to digital workflows has been gradual, fostering an adaptive and innovative work culture focused on public satisfaction and service accessibility. The study suggests that enhancing e-government infrastructure and employee training is key to improving service quality and public satisfaction in the public service context.